1997
DOI: 10.1111/j.1751-1097.1997.tb08584.x
|View full text |Cite
|
Sign up to set email alerts
|

Virucidal Treatment of Blood Protein Products with UVC Radiation

Abstract: The virus safety of blood derivatives continues to be of concern, especially with respect to nonenveloped and/or heat-stable viruses. Previously, we demonstrated that treatment of whole plasma, AHF concentrate or fibrinogen with short wavelength ultraviolet light (UVC) results in the inactivation of > or = 10(6) infectious doses (ID) of encephalomyocarditis virus (EMCV), hepatitis A virus (HAV) and porcine parvovirus (PPV), each of which is nonenveloped. Protein recovery was enhanced greatly by inclusion of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…Therefore, procedures for inactivating pathogenic viruses in these products are mandatory. Recently, however, it has received renewed attention for its capability to inactivate physically resistant non-enveloped singlestranded viruses such as Hepatitis A and parvovirus B19 [5,6]. Ultraviolet irradiation was one of the first methods investigated in the pioneering years of biopharmaceutical plasma fractionation, but soon proved ineffective at preventing transmission of ''serum hepatitis'' [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, procedures for inactivating pathogenic viruses in these products are mandatory. Recently, however, it has received renewed attention for its capability to inactivate physically resistant non-enveloped singlestranded viruses such as Hepatitis A and parvovirus B19 [5,6]. Ultraviolet irradiation was one of the first methods investigated in the pioneering years of biopharmaceutical plasma fractionation, but soon proved ineffective at preventing transmission of ''serum hepatitis'' [4].…”
Section: Introductionmentioning
confidence: 99%
“…nonenveloped and thermoresistant viruses (2,3). Several studies have reported that the use of UV-C radiation is a promising approach to the inactivation of nonenveloped viruses in plasma-fractionated products (4)(5)(6). UV-C has been known to produce lesions in DNA, predominantly cyclobutane pyrimidine dimers (CPD) and pyrimidine pyrimidone photoproducts ((6-4)PP), which are responsible for cell death (7,8), mutations (9,10) and carcinogenesis (11,12).…”
Section: Introductionmentioning
confidence: 99%
“…In particular, continuous-flow UV-C devices operating at 254 nm have been designed and their ability to eliminate viruses accurately tested [6][7][8]. The virucidal effect of UV-C radiations (100-280 nm) is due to their inherent capacity to induce the dimerization of adjacent pyrimidines in DNA and RNA, preventing subsequent replication and transcription.…”
Section: Introductionmentioning
confidence: 99%